Fiber Optic Measurement Techniques - Hui, Rongqing; O'Sullivan, Maurice (Elsevier, 2009)
This book is an indispensable collection of key optical measurement techniques essential for developing and characterizing today's photonic devices and fiber optic systems. Provided are comprehensive and systematic descriptions of various fiber optic measurement methods with the emphasis on the understanding of optoelectronic signal processing methodologies, helping the reader to weigh up the pros and cons of each technique and establish their suitability for the task at hand.